2016
DOI: 10.1139/cjfr-2016-0040
|View full text |Cite
|
Sign up to set email alerts
|

Does gender diversity in forest sector companies matter?

Abstract: Abstract:The extant literature concerned with enhancing competitiveness of forest sector companies has focused on phenomena rather than people who would drive those phenomena. Generally, human resource management research is sparse in the forest sector literature, despite well-documented knowledge that companies succeed more because of their people than because of any other factor. This article brings human resource issues to the core conversation in forest sector competitiveness research. Specifically, we foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Women are still underrepresented in the top leadership positions of the Nordic forest sector, despite high representation in higher education programs (Johansson and Ringblom 2017). Also, female members represent a 16% share in both the boards of directors and top management teams in the global top 100 pulp and paper companies (Hansen et al 2016). Positive changes in terms of increasing diversity in decision-making processes have occurred during past decades, but unequal use of power in the sector, or in society in general, may still compound unnecessary gender stereotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Women are still underrepresented in the top leadership positions of the Nordic forest sector, despite high representation in higher education programs (Johansson and Ringblom 2017). Also, female members represent a 16% share in both the boards of directors and top management teams in the global top 100 pulp and paper companies (Hansen et al 2016). Positive changes in terms of increasing diversity in decision-making processes have occurred during past decades, but unequal use of power in the sector, or in society in general, may still compound unnecessary gender stereotypes.…”
Section: Introductionmentioning
confidence: 99%
“…In a world with increasing environmental concerns, studies are showing that gender diverse boards help to improve a company's environmental policy (Li et al, 2017;Konadu, 2017). A study looking at the impact of diversity in the forestry sector found that not only was it the right thing to do as the business case demonstrates, it is the smart approach for an industry that was historically dominated by men (Hansen et al, 2016). Canada, aware of the impact of fossil fuels, has encouraged a proactive approach by companies on disclosure to investors regarding climate change risk.…”
Section: Literature History and Empirical Evidencementioning
confidence: 99%
“…In the U.S., the industry employs approximately 950,000 workers with a payroll of approximately $55 billion and manufacturing output of over $300 billion [1]. Nevertheless, the forest sector has not attracted sufficient young talent interested in a career in the industry, resulting in a graying workforce [2]. Enhancing gender diversity or the proportion of women versus men is a reliable solution for filling the workforce gap, since women make up nearly half of the labor force in North America [3], Finland [4], and Sweden [5].…”
Section: Introductionmentioning
confidence: 99%
“…This paper specifically focuses on gender as one aspect of workforce diversity due to a fact that although there are continuous efforts aimed at increasing gender diversity including in the forest sector, women are still underrepresented in its workforce [6]. There is also underrepresentation of women in top leadership in forest sector companies, even in Nordic countries that are considered at the forefront of gender equality [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation